Limites e possibilidades dos instrumentos normativos na proteção do patrimônio cultural urbano: uma análise a partir dos vieses da sustentabilidade - Rebelato, Júlia Marques (2017)
Starting from the broad universe of culture and based on a deductive analysis, the author intends to reveal the preservation of urban cultural heritage and the biases of sustainability in its multiple facets.